2016
DOI: 10.1017/ice.2016.260
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Storage Interval and Contamination of Reprocessed Flexible Endoscopes in a Pediatric Gastrointestinal Procedural Unit

Abstract: OBJECTIVE The maximum safe storage interval after endoscope reprocessing remains unknown. We assessed the association between storage interval and endoscope contamination to evaluate the need for scope reprocessing prior to use. METHODS We conducted a study in 2 phases. In phase 1, we cultured 9 gastrointestinal (GI) endoscopes that had been stored for at least 7 days since reprocessing. Each scope was cultured in 3 places: external surfaces of hand piece, insertion tube, and internal channels. In phase 2, aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…72,75,77,79 Furthermore, an endoscope storage time of under 7 days was also associated with a lower bacterial contamination rate for any pathogen compared with an endoscope storage time 14 days (OR, .43; 95% CI, .19-.99). 72,80 Notably, when restricting the analyses to only bacterial contamination with pathogenic organisms, there was no difference between endoscope storage times of <7 days and 7 days (OR, .50; 95% CI, .13-1.97) (Fig. 4).…”
Section: Suggestmentioning
confidence: 97%
See 1 more Smart Citation
“…72,75,77,79 Furthermore, an endoscope storage time of under 7 days was also associated with a lower bacterial contamination rate for any pathogen compared with an endoscope storage time 14 days (OR, .43; 95% CI, .19-.99). 72,80 Notably, when restricting the analyses to only bacterial contamination with pathogenic organisms, there was no difference between endoscope storage times of <7 days and 7 days (OR, .50; 95% CI, .13-1.97) (Fig. 4).…”
Section: Suggestmentioning
confidence: 97%
“…The storage time after which endoscopes should be reprocessed before use, termed "hang-time" or "shelflife," has been the subject of limited, small investigations. 72,[74][75][76][77][78][79][80] Eight studies have examined endoscope storage time evaluating microbial cultures in 1242 procedures. Among these studies there was tremendous variability in terms of endoscope storage time (range, 1-56 days), the timing of when the endoscope was cultured (range, 1-56 days), and which area(s) of the endoscope were cultured (varied among exterior surface, working channel, air/water/suction channels of the endoscope).…”
Section: Suggestmentioning
confidence: 99%
“…The 11 studies that constituted the final review sample are distributed as follows: PubMed (5), BVS (2), Scopus (2) and Web of Science (2). They were carried out in the Czech Republic (1) (21) , France (1) (22) , Australia (2) (23)(24) , United States (3) (25)(26)(27) and Canada (4) (4,(28)(29)(30) . Regarding the level of evidence according to Stetler et al (20) , 18% (22,30) of the selected articles correspond to level 2 (experimental studies) and 82% (4,21,(23)(24)(25)(26)(27)(28)(29) to level 3 (time series).…”
Section: Resultsmentioning
confidence: 99%
“…It was found that about a third of the publications occurred between the years 2002 and 2007 (36%) (21,(23)(24)28) , but the predominance was from the period between 2008 and 2020 (64%) (4,22,(25)(26)(27)(29)(30) , characterized by a significant increase in cases of transmission of microorganisms by flexible endoscopes.…”
Section: Resultsmentioning
confidence: 99%
“…al. [33] eine 2-phasige Untersuchung durch. In Phase 1 wurden 9 gastrointes-tinale Endoskope untersucht, die nach der maschinellen Aufbereitung mindestens 7 Tage gelagert worden waren.…”
Section: Studienlageunclassified